Rheological and Curing Behavior of a Newly Developed, Medium Viscous Acrylic Bone Cement. (9th October 2011) - Deusser, Stefan; Sattig, Christoph; Boger, Andreas
Abstract : Percutaneous vertebroplasty, comprising an injection of polymethylmethacrylate (PMMA) bone cement into vertebral bodies, is a practical procedure for stabilization of osteoporotic compression fractures and other weakening lesions. Cement leakage is considered to be the major complication. The viscosity plays a key role in this context. At high viscosity, the risk of leakage is reduced; however, injection forces are highly increased, handling time is reduced. The purpose of the study was to investigate the rheological, handling and hardening behaviour of a newly developed medium viscous bone cement at different temperatures and by simulation of a temperature shift to body-temperature. The presented data give an impression on the injectability of the cement using different sized needles. It could be concluded, that the medium viscous cement shows an adequate working time for a broad temperature range and an acceptable hardening time of around 11 min after immersing the cement into a37 ∘ C environment.